The relation between mastery goals and intrinsic motivation among university students: a longitudinal study. Issue 6 (3rd July 2017) - Bieg, Sonja; Reindl, Marion; Dresel, Markus
Abstract: The present work broadens previous research on students' mastery goals and intrinsic motivation by exploring their reciprocal effects using a longitudinal approach. To this end, a study using four measurement points was conducted during 10 weeks of one semester. The sample comprised 1156 students enrolled in psychology courses at a medium- sized university in Germany who completed questionnaires. The findings showed that both constructs were intra-individually stable over the course of one semester although the rank-order stability of mastery goals was higher than the rank-order stability of intrinsic motivation. Cross- lagged structural equation models revealed that students' mastery goals predicted their intrinsic motivation throughout the semester. However, intrinsic motivation did not predict mastery goals. Results are discussed in terms of a potential integration of achievement goal theory and self-determination theory and their practical implications.